Tinjauan Yuridis Hukuman Kebiri Perspektif Perlindungan Hak Asasi Manusia tentang Hak Memiliki Keturunan dan Hak Hidup Berkeluarga - Dioba Savana; Sobirin Malian (Ahmad Dahlan Legal Perspective, 2023)
The high levels of harassment and rape that occur in Indonesia are bad things that continue to proliferate in this country. Sexual crimes against children in Indonesia have not been able to be resolved every year by the government. According to the annual records of the National Commission on Violence against Women (Komnas Perempuan), the number of violent crimes against women in 2020 was 299,911 cases. The most significant cases were sexual violence, namely 962 cases consisting of sexual harassment (166 cases), rape (229 cases), sexual harassment (181 cases), the rest were attempted rape and other sexual violence. Since the enactment of Law No. 17 of 2016, it is expected to be a breath of fresh air for enforcement and protection, but in fact it has received rejection from the National Commission on Human Rights and the Indonesian Doctors Association. The research used in this study is normative legal research. Normative legal research is legal research that has an object of targeting laws and regulations, and other legal materials. This data collection method is a way to collect the materials needed in a research that can be done by means of literature research (literature research). Based on the results of the research and discussion, it can be explained as follows: first, there are violations of human rights and legal norms in the article which contains chemical castration for the perpetrators if it is related to the protection of the rights to have a family and have children Against Article 28B Paragraph (1) of the 1945 Constitution which in Article The provisions clearly emphasize that everyone has the right to form a family and continue offspring through a legal marriage. Second, castration is one of the actions to limit the right of every person to have offspring. Third, the chemical castration punishment referred to in Law number 17 of 2016 is an inhumane and inaccurate act, so that the punishment violates human rights. Fourth, in view of the theory of legal objectives, this castration punishment has not really been implemented clearly. in implementing legal certainty, justice and benefits for society and the legal norms themselves.